2013
DOI: 10.2753/ces1097-1475460104
|View full text |Cite
|
Sign up to set email alerts
|

Technological Capacity, Product Position, and Firm Competitiveness

Abstract: using firm-level data from a 2009 survey conducted in Suzhou city, jiangsu province, this article examines the impact of technological capacity and value-chain position on a firm's product competitiveness. Technological capacity and product competitiveness are self-assessed relative to other firms and products in the same industry. Position on the value chain is measured relative to a firm's position as an original-brand manufacturer or not. Our empirical results show that competitiveness rises with a firm's t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Exports of textile goods created many employment opportunities and helped the industrialization of Japan. In contrast, India did not have technological capabilities to modify 2 At the micro level, Ju, Fung, and Mano (2013) have studied how a firm's performance is affected by technological capabilities, and Gao et al (2013) have shown that a firm's competitiveness increases with its technological capacity. imported machines and the development of the textile industry lagged (Otsuka, Ranis, and Saxonhouse, 1988).…”
Section: The Importance Of Technological Capability In the Manufacturmentioning
confidence: 99%
“…Exports of textile goods created many employment opportunities and helped the industrialization of Japan. In contrast, India did not have technological capabilities to modify 2 At the micro level, Ju, Fung, and Mano (2013) have studied how a firm's performance is affected by technological capabilities, and Gao et al (2013) have shown that a firm's competitiveness increases with its technological capacity. imported machines and the development of the textile industry lagged (Otsuka, Ranis, and Saxonhouse, 1988).…”
Section: The Importance Of Technological Capability In the Manufacturmentioning
confidence: 99%
“…Buckley et al (1988) define firm competitiveness as consisting of three dimensions: performance, potential, and process. Craig et al (2008), Laureti -Viviani (2011), and Gao et al (2013) conclude that performance is an important dimension of firm-level competitiveness. Kivilouto (2013) asserts that firm performance itself consists of multiple dimensions, and is characterised by the co-existence of growth (potential) and profitability (performance).…”
Section: Competitivenessmentioning
confidence: 99%
“…Craig et al (2008) use self-reported scales measuring firm performance and two different dimensions of competitive orientation in pursuit of measuring competitiveness. Gao et al (2013) also implemented self-rated measures of competitiveness, consisting of product competitiveness, technological capacity, and the product position on the value chain. A fourth aspect of firm competitiveness was included in the modelling by Gao et al (2013), namely firm size, in order to incorporate a measure of organisational capacity.…”
Section: Competitivenessmentioning
confidence: 99%
See 2 more Smart Citations